2014
DOI: 10.1007/s11999-013-3248-4
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Cement-bone Interlock in Retrieved Tibial Components from Total Knee Arthroplasties

Abstract: Background Aseptic loosening continues to be a shortand long-term complication for patients with cemented TKAs. Most studies to this point have evaluated tibial component fixation via radiographic changes at the implant-bone interface and quantification of component migration; direct assessment of morphologic features of the interface from functioning TKAs may provide new information regarding how TKAs function and are fixed to bone. Questions/purposes In a postmortem retrieval study, we asked: (1) What are th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
64
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 20 publications
2
64
0
Order By: Relevance
“…Bone-cement interface integrity has been identified as the critical element in the success and longevity of both hip and knee cemented replacements (Gardiner & Hozack, 1994;Stocks et al, 1995;Thanner et al, 1999;Zant et al, 2008;Wang et al, 2009;Tozzi et al, 2012;Goodheart et al, 2014;Howard et al, 2014;Miller et al, 2014Miller et al, , 2014b. Principal concerns regarding the performance of cemented fixation in the hip were related to fatigue damage accumulation in the cement mantle in femoral (Cristofolini et al, 2007;Race et al, 2003Race et al, , 2011 and acetabular (Heaton-Adegbile et al, 2006;Zant et al, 2007;Tong et al, 2008) components.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone-cement interface integrity has been identified as the critical element in the success and longevity of both hip and knee cemented replacements (Gardiner & Hozack, 1994;Stocks et al, 1995;Thanner et al, 1999;Zant et al, 2008;Wang et al, 2009;Tozzi et al, 2012;Goodheart et al, 2014;Howard et al, 2014;Miller et al, 2014Miller et al, , 2014b. Principal concerns regarding the performance of cemented fixation in the hip were related to fatigue damage accumulation in the cement mantle in femoral (Cristofolini et al, 2007;Race et al, 2003Race et al, , 2011 and acetabular (Heaton-Adegbile et al, 2006;Zant et al, 2007;Tong et al, 2008) components.…”
Section: Introductionmentioning
confidence: 99%
“…On the acetabular side the cracking in the cement mantle seems to be limited compared to the femoral counterpart and other failure mechanisms, such as debonding at the bone-cement interface, are mainly responsible for the implant loosening Wang et al, 2009;Tozzi et al, 2012). With regards to bone-cement fixation in the knee, a number of recent studies reported how the loss of interlock between bone and cement following in vivo service may eventually jeopardise the performance of both tibial Miller et al, 2014Miller et al, , 2014b and femoral (Howard et al, 2014) components over time. Goodheart et al (2014) also showed how such ex vivo loss of interlock resulted in a reduced strength of the bone-cement fixation in total knee arthroplasty (TKA).…”
Section: Introductionmentioning
confidence: 99%
“…The initial interdigitation depth (inID) was used to estimate the initial extent of interlock between cement and bone at the completion of surgery [12]. A line was drawn at the furthest initial extent of bone into cement, as documented by the cement mold (Line 1, Figure 2C).…”
Section: Methodsmentioning
confidence: 99%
“…The percent difference between inID and curID (inID-curID/inID) defined the loss of interdigitation depth (lossID) and represented an estimate of how much trabecular bone was resorbed during in vivo service. The estimated error in determining the inID has been reported to be 0.06mm [12] using lab-prepared constructs where there was no bony resorption.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation